The effect of augmented reality mobile learning in microeconomic course - Dayana Farzeeha Ali; Nusaila Johari; Aimi Ruzaini Ahmad (International Journal of Evaluation and Research in Education (IJERE), 2023)
Recently, there has been a surge of interest for students to use technology while engaging in their learning. Augmented reality is one of the technologies found suitable for use in the educational field, such as in science, mathematics, and engineering. However, it is not yet being explored in the Microeconomics course. Therefore, this study investigated the effectiveness of using augmented reality, namely Augmented Reality Mobile Learning in Microeconomic courses (ARMLAAPPS). This study used a quasi-experimental design, and two groups were involved: the control and experimental groups. They are undergoing teaching and learning sessions using ARMLAAPPS and conventional teaching methods. This study indicates that students in the experimental group showed a significantly higher visualization skills level than those in the control group after teaching and learning. Besides, this study also found that ARMLAAPPS can assist in highlighting student-centered learning, stimulating student interest and curiosity, increasing student cognitive, affective, and psychomotor processes, and increasing student involvement in the information-seeking process. Educators are suggested to use augmented reality in their teaching and learning since it has effectively enhanced students’ visualization skills and promoted a better understanding of knowledge.